2021
DOI: 10.1029/2021gl094681
|View full text |Cite
|
Sign up to set email alerts
|

First Observations of O2+ Band EMIC Waves in the Terrestrial Magnetosphere

Abstract: Although electromagnetic ion cyclotron (EMIC) waves are often known to exhibit three (H+, He+, and O+) usual bands, other peculiar minor ions (excluding He+ and O+) might also play an important role in the spectra of EMIC waves. This letter reports an interesting case that He+ band EMIC waves appear to split into O2+ and He+ band emissions. Wave frequency spectra suggesting that the organization of the wave emissions by the O2+ gyrofrequency motivates an investigation of the effects of O2+ presence on EMIC wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…In the Jovian and Saturnian magnetosphere, the anisotropy can result from the pickup process of newly generated ions near the erupting moons (Io and Enceladus, see Kivelson et al., 1996; Leisner et al., 2006; Russell et al., 2006). In the near‐Earth space, a primary source of EMIC waves is the anisotropy developed after the injection of magnetotail ions into the inner magnetosphere (Baker et al., 1982; Birn et al., 1998; Sergeev et al., 2012; Yu et al., 2021). Recognizing that perpendicular‐moving ions (with equatorial pitch angle of ∼90°) drift faster in the magnetic dipole field than bouncing ions (with equatorial pitch angle closer to 0 ${0}^{\circ }$ or 180 ${180}^{\circ }$) (Hamlin et al., 1961), the Earth's dipole field in the inner magnetosphere serves as a natural filter to gradually separate ions with different pitch angles, which facilitates the EMIC wave excitation as evidenced by the strong association between nightside particle injections and EMIC wave activities (Chen et al., 2010; Jordanova et al., 2008; Jun et al., 2019; Remya et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In the Jovian and Saturnian magnetosphere, the anisotropy can result from the pickup process of newly generated ions near the erupting moons (Io and Enceladus, see Kivelson et al., 1996; Leisner et al., 2006; Russell et al., 2006). In the near‐Earth space, a primary source of EMIC waves is the anisotropy developed after the injection of magnetotail ions into the inner magnetosphere (Baker et al., 1982; Birn et al., 1998; Sergeev et al., 2012; Yu et al., 2021). Recognizing that perpendicular‐moving ions (with equatorial pitch angle of ∼90°) drift faster in the magnetic dipole field than bouncing ions (with equatorial pitch angle closer to 0 ${0}^{\circ }$ or 180 ${180}^{\circ }$) (Hamlin et al., 1961), the Earth's dipole field in the inner magnetosphere serves as a natural filter to gradually separate ions with different pitch angles, which facilitates the EMIC wave excitation as evidenced by the strong association between nightside particle injections and EMIC wave activities (Chen et al., 2010; Jordanova et al., 2008; Jun et al., 2019; Remya et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that the spectral properties of EMIC waves are also affected by other minor heavy ions such as nitrogen ions (N + ) and doubly charged oxygen ions (O 2+ ) in the terrestrial magnetosphere (Bashir & Ilie, 2018, 2021; Yu et al., 2021). The small fraction of heavy ion concentration changes the EMIC wave properties.…”
Section: Introductionmentioning
confidence: 99%
“…Since the parallel data is absent in satellite measurements, in our modeling, protons below 300 eV are assumed to be a multicomponent Maxwellian distribution. The final parameters of the modeled distribution are displayed in Table 1, where each component is modeled as a ring‐beam distribution defined as follows (Min et al., 2016; Yu, Yuan, & Ouyang, 2021) frb=nrbCrπ3/2VV2evVdV2evVrV2 ${f}_{rb}=\frac{{n}_{\text{rb}}}{{C}_{r}{\pi }^{3/2}{V}_{{\Vert} }{V}_{\perp }^{2}}{e}^{-{\left(\frac{{v}_{{\Vert} }-{V}_{d}}{{V}_{{\Vert} }}\right)}^{2}}{e}^{-{\left(\frac{{v}_{\perp }-{V}_{r}}{{V}_{\perp }}\right)}^{2}}$ where n rb , V d , V r , V ∥ , and V ⊥ are the number density, drift speed, ring speed, and parallel and perpendicular thermal speeds, respectively. Such a ring‐beam distribution will degenerate into a ring distribution for a vanishing drift speed ( V d = 0), into a beam distribution for a vanishing ring speed ( V r = 0), and into a Maxwellian distribution for both vanishing ring and drift speeds ( V r = V d = 0).…”
Section: Observationsmentioning
confidence: 99%
“…However, MS waves are found to propagate in both radial and azimuthal directions (Xiao et al., 2012). When propagating radially inward, their frequencies might fall below the local proton gyrofrequency and be reflected back near the cut‐off region (Santolík et al., 2016; Yu, Yuan, and Yao, 2021). It has been demonstrated that MS waves can play an important role in the dynamic evolution of the magnetospheric particles, especially in the formation of the butterfly distribution for the radiation belt electrons through resonant interactions and/or the transit‐time effect (J. Li et al., 2016; J. Yu et al., 2019; S. Fu et al., 2019; Xiao et al., 2015; X. Yu et al., 2020; Yuan, Yu, et al., 2018).…”
Section: Introductionmentioning
confidence: 99%